(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Sudden cardiac death (SCD) refers to the unexpected death of an individual occurring within one hour of symptom onset or within 24 hours of last being seen in good health if the death is unwitnessed. Since virtual autopsy is finding its way globally, the applications of postmortem computed tomography (PMCT) in cases of sudden cardiac death, which forensic pathologists frequently encounter, should be fostered and further developed. This case report discusses the sudden death of a 60-year-old male who had an acute on chronic infarct in the left ventricle and multiple foci of calcifications in the coronary arteries and the aorta. Though coronary and aortic calcifications were clearly visualised by PMCT, the critical patency of the lumen at the site of occlusion and the myocardial pathology could not be adequately visualised. PMCT angiography (PMCTA) was performed subsequently, which provided excellent visualisation of the luminal patency of coronary vessels, thereby augmenting the efficiency and diagnostic yield of virtual autopsy. Additionally, in resource-lim ited settings like India, where cost-effectiveness is a major factor, barium-based contrast agents have been tried in this case as an alternative to Iohexol (iodine-based agents), and the challenges faced in such scenarios are also comprehen sively discussed with a forward-looking perspective on future improvements.